NPBS database: a chemical data resource with relational data between natural products and biological sources. (11th December 2020) - Xu, Tingjun; Chen, Weiming; Zhou, Junhong; Dai, Jingfang; Li, Yingyong; Zhao, Yingli
Abstract: NPBS (Natural Products & Biological Sources) database is a chemical data resource with relational data between natural products and biological sources, manually curated from literatures of natural product researches. The relational data link a specific species and all the natural products derived from it and contrarily link a specific natural product and all the biological sources. The biological sources cover diverse species of plant, bacterial, fungal and marine organisms; the natural molecules have proper chemical structure data and computable molecular properties and all the relational data have corresponding references. NPBS database provides a wider choice of biological sources and can be used for dereplication to prevent re-isolation and re-characterization of already known natural products. Database URL : http://www.organchem.csdb.cn/scdb/NPBS